Effect of Age on Cadre Ability in Early Detection of High Domestic Violence - Yulianti, Yulianti (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2021)
Cases of Domestic Violence have a big impact on someone who experiences it even to the point of experiencing depression which even causes a sense of wanting to end his life[7]. Factors causing the high incidence of domestic violence are things that often occur such as economic factors, lack of communication, infidelity even to the point of personality characteristics being one of the causes[8]. The role of cadres is important in the process of empowering victims of domestic violence who play a role in community elements to overcome domestic violence events[5]. The purpose of this study was to determine the factors that influence the level of cadre's ability to carry out early detection of domestic violence in the Work Area of the Sleman Health Center, Yogyakarta. This study used a cross sectional design involving a cadre population of 586 cadres with purposive sampling technique. Statistical analysis used the Eta Correlation test with the results of the statistical test of the ability of cadres in early detection of domestic violence with a significant value of 0.024. The conclusion of the statistical test results in this study is that the age of cadres has a relationship with the ability of cadres to carry out early detection of domestic violence in the Godean II Health Center Work Area, Yogyakarta.Keywords: